Characterization of blueberry fruits (Vaccinium spp.) and derived products - Reque,Priscilla Magro (2014)
The objectives of this study were to physicochemically characterize and determine the antioxidant activities and anthocyanin contents of organic Rabbiteye blueberries grown in Southern Brazil and its derived products, in order to investigate the utility of food processing wastes as raw materials for developing products with beneficial health properties. The antioxidant capacity of the blueberries was superior to that of other fruits and juices. The pomace exhibited high activity, albeit lower than that of the fruit, while the flour and the dried blueberries lost 66% and 46% of the original antioxidant activity, respectively. The average anthocyanin contents of the fruits were moderate compared to other sources and species of blueberries. The pomace contains a large amount of anthocyanins while the flour and dried blueberries exhibited a 32% and 42% loss in anthocyanin content, respectively. The use of agro-industrial residues, in addition to adding value and minimizing the impact caused by the accumulation in the environment, can be directed toward the development of new products with bioactive properties.